2009
DOI: 10.1007/s11064-009-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Their Interactions with Diazepam on Modulation of Serum Corticosterone Concentration in Male Mice

Abstract: Experimental results indicate a mutual interaction between cannabinoidergic and GABAergic systems; however, the interaction between these systems on corticosterone release has not been fully investigated. In this study, we treated male mice with either cannabinoid compounds alone or in combination with diazepam. Blood samples were collected at 60 min post-injection. The serum corticosterone (CORT) level was measured using ELISA technique. Acute treatment of mice by cannabinoid receptor agonist WIN55212-2 (2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(53 reference statements)
2
4
0
Order By: Relevance
“…In vivo studies showed that low doses of CB 1 R agonists other than THC reduced basal and stress-induced HPA axis responses in rodents Saber-Tehrani et al 2010), data that are consistent with the regulatory mechanisms discussed above. However, high doses of synthetic agonists , and THC treatment, increase circulating concentrations of CORT (Steiner and Wotjak 2008).…”
Section: Cannabinoids and The Hypothalamic-pituitary-adrenal Axissupporting
confidence: 77%
“…In vivo studies showed that low doses of CB 1 R agonists other than THC reduced basal and stress-induced HPA axis responses in rodents Saber-Tehrani et al 2010), data that are consistent with the regulatory mechanisms discussed above. However, high doses of synthetic agonists , and THC treatment, increase circulating concentrations of CORT (Steiner and Wotjak 2008).…”
Section: Cannabinoids and The Hypothalamic-pituitary-adrenal Axissupporting
confidence: 77%
“…Some studies suggest that neurogenesis may also be modulated by the correlation between the cannnabinoid and the corticosteroid systems. Thus, AM251 blocks the effect of the endocannabinoid reuptake inhibitor AM404 and the endocannabinoid degradation enzyme inhibitor URB597 on the increase of plasma corticosterone levels (Saber‐Tehrani et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the hypothalamic content of anandamide is highest at the times of 07:00 and 11:00 and low between 15:00 and 03:00 57 . In vivo studies demonstrate that low doses of CB1 agonists other than THC reduced basal and stress-induced HPA pathway responses in rodents 58, 59 . In persons who were either naıve to cannabis or infrequent users, acute consumption of cannabis 60 or THC 61, 62 increased secretion of cortisol.…”
Section: Endocannabinoids Chronic Stress and Painmentioning
confidence: 99%